Pengaruh Soft Power Korea dalam Budaya Korean Wave Sebagai Eksistensi Identitas Nasional - Ameilia, Fuji; Rifai, Maulana Putri; Marsingga, Prilla Putri (Jurnal Ilmiah Wahana Pendidikan, 2025)
Korean Wave is a term that refers to the global spread of Korean pop culture in various countries around the world starting from the 1990s. The phenomenon of the Korean Wave or Korean Wave is currently experiencing rapid development. This phenomenon is growing rapidly not only in Indonesia but also in the world. Through this, the South Korean government utilizes the Korean Wave as an instrument of their soft power. This study aims to find out how South Korea's soft power can affect Indonesia's national identity. This type of research is descriptive, using a qualitative approach. The results is that the Korean Wave can be easily accepted and affect the lifestyle and national culture that exists, especially for young people, so that unconsciously the influence of Korean soft power in the Korean Wave phenomenon can also have an impact on cultural threats that exist in Indonesia as a national identity.